Tandem language learning on the Internet : theory, tool development and empirical exploration - Appel, Marie Christine (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2004)
The objective of this thesis is to investigate and advance the use of electronic mail for tandem language learning. Earlier research raised the following primary issues. Firstly, there were some organizational problems rising from the use of e-mail tandem. Secondly, there appeared to be a disparity between the potential for language learning and its low level of realization, and a disparity between the initial enthusiasm participants show and the low levels of sustainability of these exchanges. Finally, the lack of a comprehensive descriptive evaluation of the language used in one-to-one e- mail and more specifically in the context of tandem learning, made it impossible to establish the utility of e-mail tandem as a language learning tool. Through the exploration of theory, tool development and empirical exploration, this thesis addresses all three issues in a cyclic sequence of studies.
Keywords: Applied Linguistics, Ph.D.; Ph.D. Trinity College Dublin